Cytotoxicity of Alpinia galanga Rhizome Crude Extract on NIH-3T3 Cells - Ferry Sandra; Janti Sudiono; Pretty Trisfilha; Deviyanti Pratiwi (The Prodia Education and Research Institute (PERI), 2017)
BACKGROUND: Alpinia galanga (A. galanga) was reported as a potential medicinal source due to its wide effect. A. galanga rhizome crude extract (ARCE) was reported to have high cytotoxic effect in cancer cells, but low in normal cells. However half maximal inhibitory concentration (IC50) of ARCE is not clearly known yet. Hence, current study was conducted to investigate the IC50 of ARCE in normal standard fibroblast cell line, NIH-3T3 cells.METHODS: Rhizomes of A. galanga were collected, peeled, dried, milled and weighed. Extraction was performed using maceration method, then filtered and evaporated. ARCE with various concentrations were applied in NIH-3T3 cells for 24 or 48 hours. Cells were documented and counted with 3-(4,5-dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium bromide (MTT) assay.RESULTS: Five hundreds grams of simplicia were macerated with ethanol and evaporated, 1 mg/mL crude extract with total volume of 114 mL was obtained. By addition of ARCE in NIH-3T3 cell culture, number of NIH-3T3 cells were shown less when treated with higher concentration of ARCE. Cell numbers of 0, 3.125, 6.25, 12.5, 25 and 50% ARCE treatment for 24 hours are 11,531, 11,352, 10,920, 10,365, 9,471, 8,360, respectively, meanwhile for 48 hours are 13,219, 12,686, 12,278, 11,390, 10,279, 8,390, respectively.CONCLUSION: IC50 of ARCE in 24 hours treatment was 620.5 mg/mL, while in 48 hours treatment was 666.6 mg/mL. Hence, ARCE is suggested to have low cytotoxic effect in NIH-3T3 cells.KEYWORDS: Alpinia galanga, ginger, extract, cytotoxic, MTT, NIH-3T3